A7.6 Comparative Transcriptome Analysis of Human and Mouse Synovial Fibroblast Responses to TNF. (25th February 2013) - Häupl, Thomas; Sörensen, Till; Smiljanovic, Bijana; Bonin, Marc; Grützkau, Andreas; Nikolaou, Christoforos; Pandis, Ioannis; Kollias, George; Rowe, Anthony
Abstract : Background and Objectives: Animal models are essential for development of new therapeutics to test their effectiveness and to control for side effects. Targeted therapies with biologics reveal differences in responsiveness and suggest substantial differences in the molecular pathomechanisms of human as well as murine arthritis. In order to characterise such differences, we started a pilot investigation based on published transcriptomes to develop bioinformatic strategies of interspecies gene expression comparison. Materials and Methods: A GEO repository search for compatible data sets on arthritis in human and mouse revealed the Affymetrix based transcriptomes of synovial fibroblasts from rheumatoid arthritis (RA) and osteoarthritis (OA) patients (GEO-accession: GSE13837) and mouse BALBc wt (GSE17160) with similar stimulation (TNF-alpha) and time point after stimulation (12 hours). MAS5 algorithms of signal extraction and pairwise comparison were performed. The BioRetis database was used for group comparisons, candidate gene selection and data sharing. Differentially expressed genes were exported for interspecies comparison in a filemaker database. Affymetrix annotation files were used for mapping of orthologous genes. Results: The number of differentially expressed genes induced by TNF in synovial fibroblast from RA, OA and BALBc were 1584, 1476 and 503 respectively. Comparison of genes overexpressed in RA and OA revealed up to 70% (1034 genes) overlap. Murine and human response was similar for 197 genes in all three groups, 45 only between BALBc and RA and 24 only between BALBc and OA. Ranking the genes by dominance in change call and/or fold change, 7 genes were overlapping between the top 10 of both human cells, OA and RA, and 13 out of the top 20. All overlapping genes in human revealed a high correlation (R = 0.795). In contrast, overlap between RA and BALBc SFbl responses revealed only 4 genes out of the top 10 and 5 out of the top 20 in each and a weaker correlation (0.392). Pathway tools including IPA may identify TNF as one potential upstream regulator. However, the reference list of expected gene candidates for scoring in IPA seemed to be about 2.5 fold longer in human and to include less than 60% of the murine reference candidates. Conclusions: Interspecies comparison in this defined experiment revealed first insight in common responses but also demonstrates that differences can be observed even in most dominant candidate genes. Therefore, systematic investigations are needed to provide a reliable basis for comparative mapping of the molecular pathomechanisms in mouse models and human disease. Acknowledgement: BTCure IMI grant agreement no. 115142